2021
DOI: 10.1126/science.abg7917
|View full text |Cite
|
Sign up to set email alerts
|

Plant “helper” immune receptors are Ca 2+ -permeable nonselective cation channels

Abstract: Plant nucleotide-binding leucine-rich repeat receptors (NLRs) regulate immunity and cell death. In Arabidopsis, a subfamily of “helper” NLRs are required by many “sensor” NLRs. Active NRG1.1 oligomerized, was enriched in plasma membrane puncta and conferred cytoplasmic Ca2+ influx in plant and human cells. NRG1.1-dependent Ca2+ influx and cell death were sensitive to Ca2+ channel blockers and were suppressed by mutations impacting oligomerization or plasma membrane enrichment. Ca2+ influx and cell death mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
322
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 274 publications
(339 citation statements)
references
References 66 publications
14
322
2
1
Order By: Relevance
“…The different NLR classes are therefore also termed as TNLs (with a TIR domain), CNLs (with a CC domain) and RNLs (harboring a CC R domain). The CC and CC R domains share structural homology with the N-terminal 4-helical bundle of mammalian and plant mixed-linage kinase like (MLKL) proteins and poreforming fungal HET-s/Helo domain containing proteins [24][25][26][27][28][29]. TIR domains have been shown to be structurally and functionally conservedat least to some extentand can be found in prokaryotic and other eukaryotic organisms [30,31], where TIR domain-containing proteins have also been implicated in immunity and initiation of cell death responses [32][33][34].…”
Section: Nlr Domains and Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…The different NLR classes are therefore also termed as TNLs (with a TIR domain), CNLs (with a CC domain) and RNLs (harboring a CC R domain). The CC and CC R domains share structural homology with the N-terminal 4-helical bundle of mammalian and plant mixed-linage kinase like (MLKL) proteins and poreforming fungal HET-s/Helo domain containing proteins [24][25][26][27][28][29]. TIR domains have been shown to be structurally and functionally conservedat least to some extentand can be found in prokaryotic and other eukaryotic organisms [30,31], where TIR domain-containing proteins have also been implicated in immunity and initiation of cell death responses [32][33][34].…”
Section: Nlr Domains and Structuresmentioning
confidence: 99%
“…( 3 ) How the EDS1/PAD4 or EDS1/SAG101 RNL components are activated by TIR domain NADase activity is not clear. Recently, it was shown that the Arabidopsis NRG1.1/NRG1A and ADR1 (both RNLs) can form activation-dependent oligomers and function also as calcium permeable cation channels at the plasma membrane [ 27 , 64 ]. Note: There is no experimental evidence yet that RNL resistosomes form ring-like structures (here a hexamere), which are similar to the pentameric ZAR1 ring-like resistosome.…”
Section: Effector Recognition and Nlr Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since there is no evidence so far for direct interaction between NRCs and corresponding sensor NLR partners, does SS15 binding interfere with downstream signaling steps that are required for cell death execution? Recent studies uncovered that the activated sensor NLR, ZAR1, and the helper-NLRs, NRG1, and ADR1 function as cation channels that promote calcium influx leading to HR cell death [8,9]. Since the N-terminal MADA motif of NRCs, which is sufficient to induce cell death, is functionally conserved in ZAR1 and the larger MADA-CC-NLR family [10], NRCs are more likely to function through similar mechanisms by forming cation channels.…”
mentioning
confidence: 99%